A welding task data model for intelligent process planning of robotic welding. (August 2020) - Shen, Weidong; Hu, Tianliang; Zhang, Chengrui; Ye, Yingxin; Li, Zhengyu
Highlights: A welding task data model which includes sufficient information is proposed to solve the problems of inaccuracy and incompleteness of information in process planning. EXPRESS is adopted to design the welding task data model in detail for more expandability. The proposed welding task data model is demonstrated through creating the welding task file of an automobile front door subassembly. The welding task file is defined in format of STEP that supports expandability and information integration of robotic welding. An application framework of the welding task file is presented. Results show that proposed welding task data model is feasible for supporting intelligent process planning and information integration of robotic welding. Abstract: Nowadays, as an efficient and automatic welding machine that accepts and executes human instructions, welding robots are widely used in industry. However, the lack of intelligence in process planning makes welding preparation complex and time-consuming. In order to realize intelligent process planning of robotic welding, one of the key factors is designing a welding task data model that can support process planning. However, current welding task models have some drawbacks, such as inaccurate geometry information, lacking information on welding requirements, and lacking consideration of machine-readability and compatibility. They cannot provide sufficient information for intelligent process planning. In this paper, a welding task data model, which includes information on accurate geometry, dimension and welding requirement, is presented to solve these problems. Firstly, through requirement analysis, necessary information items of a welding task data model are analyzed and summarized. Then the welding task data model is designed in detail by using EXPRESS. The feasibility of proposed welding task data model is demonstrated through creating the welding task file of an automobile front door subassembly. Moreover, an application framework of the welding task file is presented. Results show that proposed welding task data model is feasible for supporting intelligent process planning and information integration of robotic welding.